Situation Report: Hungary, 20 January 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungarian Writers' Union Meets First National Conference of Workshop Supervisors Regulations on Reduced Working Time and Annual Vacations Disc Jockeys in the Limelight Agricultural Cooperative Congress Takes Stock and Sets Future Tasks Sandor Bali, Budapest Workers' Council Leader in 1956, Dies